UZBEK SCIENTISTS ABOUT THE UPPER KARAKALPAKS IN THE POST-INDEPENDENCE PERIOD - Prekeeva, Amangul; Kutlimuratov, Ilhamjan (SCIENCE and SOCIETY, 2026)
This article is devoted to the information published in the scientific literature by Uzbek scientists about the upper Karakalpaks in the post-independence period.
Keywords: national identity; history of the Karakalpaks; upper Karakalpaks; Fergana Valley; Bukhara Karakalpaks; Surkhandarya; Khomkan Karakalpaks; animal farming; farming; boyrashiliq (made of reeds that protect the windows from sunlight); Karakalpak tribes; language; history; customs and traditions